2003
DOI: 10.1002/ar.a.10090
|View full text |Cite
|
Sign up to set email alerts
|

Smad 3 regulates proliferation of the mouse ovarian surface epithelium

Abstract: Smad 3 is a signaling intermediate for the transforming growth factor beta (TGF␤) family; however, little is known about the role this protein plays in the regulation of the ovarian surface epithelium (OSE). Using a transgenic mouse model, we found that in the absence of Smad 3 there was a distinct morphological alteration of OSE cells. Wild-type (WT) OSE was flat with thin cells, while Smad 3-deficient (Smad 3 -/-) OSE was thick with plump cuboidal cells. WT OSE had less immunostaining for proliferating cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The siRNA study also demonstrated an important role for Smad3 in ER expression. Consistent with our results, in a study investigating involvement of Smad3 in ovarian surface epithelium (OSE) proliferation, it was shown that ER␣ expression is dramatically decreased in OSE of Smad3 homozygous knock-out mice compared with wild type mice (74). Smad3 can bind to DNA directly, and an 8-bp palindromic sequence 5Ј-GTCTAGAC-3Ј has been identified as a Smad binding element for the highly conserved MH1 domain of human Smad3 and -4 (73).…”
Section: Discussionsupporting
confidence: 79%
“…The siRNA study also demonstrated an important role for Smad3 in ER expression. Consistent with our results, in a study investigating involvement of Smad3 in ovarian surface epithelium (OSE) proliferation, it was shown that ER␣ expression is dramatically decreased in OSE of Smad3 homozygous knock-out mice compared with wild type mice (74). Smad3 can bind to DNA directly, and an 8-bp palindromic sequence 5Ј-GTCTAGAC-3Ј has been identified as a Smad binding element for the highly conserved MH1 domain of human Smad3 and -4 (73).…”
Section: Discussionsupporting
confidence: 79%
“…A lower OSE cell height is indicative of an antiproliferative effect, as metaplastic changes of OSE are associated with columnar cell shapes and shorter cell morphology was reported to be associated with the presence of (putative) tumor suppressors (Smad 3, ERβ1) in the mouse (Symonds et al, 2003;Gulliver and Hurst, 2011). The reduction in OSE cell height was more pronounced in the DZ-exposed group than in the group exposed to EE.…”
mentioning
confidence: 84%
“…Sections were cut at 5 m and subjected to staining for PCNA using a commercially available monoclonal antibody (1:100 dilution; Oncogene Research Products, Boston, MA) as described previously (22,24). The biotinylated streptavidin Histomouse-SP system (Zymed Laboratories, Inc., San Francisco, CA) with background blocking was used with 3-amino-9-ethyl carbazole chromogenic visualization and Mayer's hematoxylin counterstaining.…”
Section: Measurement Of Proliferation In the Ovarymentioning
confidence: 99%
“…Downstream Smad signaling proteins might be the essential determinants of the different actions of TGF␤ superfamily members, but little is known about their function in the mammalian ovary. Smad3 is a receptor regulated Smad, and it is highly expressed in the ovarian surface epithelium, granulosa cells, and oocytes of several animal models (21)(22)(23)(24). Smad3 and its closely related homolog Smad2, mediate intracellular signaling pathways from TGF␤ and activin, each of which has been implicated as an important factor in ovarian development and function (3,4).…”
mentioning
confidence: 99%